Plant clinic training system - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Plant Clinic: a training system for decision-making and resource management in plant disease diagnosis by R Black, A Sweetmore and J Holt 1995 19pp + floppy disk price UKL 10.00 ISBN 0 85954 396 X